2018
DOI: 10.1007/s00248-018-1288-8
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Habitat and Phylogeny on the Skin Microbiome of Amphibians in Guatemala and Mexico

Abstract: Microbial symbionts are increasingly recognized as playing a critical role in organismal health across a wide range of hosts. Amphibians are unique hosts in that their skin helps to regulate the exchange of water, ions, and gases, and it plays an active role in defense against pathogens through the synthesis of anti-microbial peptides. The microbiome of amphibian skin includes a diverse community of bacteria known to defend against pathogens, including the global pandemic lineage of Batrachochytrium dendrobati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 55 publications
(81 reference statements)
1
24
1
Order By: Relevance
“…Changes in environmental conditions are known to influence the microbiome [4,6,7], potentially affecting the hosts ability to resist infection by a pathogen [18,19]. In this study we have reported on the microbial community associated with R. sylvatica skin over the course of multiple seasons to observe the changes in community composition and structure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes in environmental conditions are known to influence the microbiome [4,6,7], potentially affecting the hosts ability to resist infection by a pathogen [18,19]. In this study we have reported on the microbial community associated with R. sylvatica skin over the course of multiple seasons to observe the changes in community composition and structure.…”
Section: Discussionmentioning
confidence: 99%
“…Core taxa were determined for each group of seasonal frog skin communities, and for the overall frog skin microbiome, using the core-features command in QIIME2. Core taxa were defined as those found to be present in 90% or more of the samples within a given group, as this is a commonly used threshold [6,38] which meets the definition of core microbiota as those which are commonly present within samples from a given environment [39]. Venn diagrams depicting the overlap of seasonally core microbiota were prepared using the online Venn diagram tool provided by the University of Ghent (http://bioinformatics.psb.ugent.be/webtools/Venn/).…”
Section: Taxonomic Assignment and Significancementioning
confidence: 99%
See 1 more Smart Citation
“…The establishment of the microbial skin community in amphibians is mainly obtained on the vertical transmission of parental microbes, horizontal transmission (e.g., during mating), pool of microbes present in the external environment (both aquatic and terrestrial), and on the interaction between the host’s immune system/mucous composition with bacteria [ 21 , 29 , 34 , 35 ]. Beyond this, the skin microbial community can be influenced by several biotic and abiotic environmental factors like chemical contamination [ 4 , 33 , 35 , 36 , 37 , 38 ]. However, the research about the influence of pollution on the skin microbiome composition is starting to understand how these changes are achieved.…”
Section: Introductionmentioning
confidence: 99%
“…This coincided with variation in both the bacterial and fungal communities of salamanders found at these sites. We believe our findings provide valuable insight into the exogenous factors often confounded by host species identity, a well-supported predictor of microbial composition (Ellison et al, 2018;Jani & Briggs, 2018;Muletz-Wolz et al, 2018). Additionally, this study reveals the important roles that dispersal, drift, and heterogeneous selection play in driving dissimilarity between individual hosts.…”
Section: Discussionmentioning
confidence: 57%